2021
DOI: 10.3390/cancers13092025
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Colorectal Cancer in Terms of Epidemiology, Risk Factors, Development, Symptoms and Diagnosis

Abstract: This review article contains a concise consideration of genetic and environmental risk factors for colorectal cancer. Known risk factors associated with colorectal cancer include familial and hereditary factors and lifestyle-related and ecological factors. Lifestyle factors are significant because of the potential for improving our understanding of the disease. Physical inactivity, obesity, smoking and alcohol consumption can also be addressed through therapeutic interventions. We also made efforts to systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
247
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 439 publications
(352 citation statements)
references
References 140 publications
0
247
1
1
Order By: Relevance
“…46 The risk of development of CRC due to a high-fat diet is thought to be due to exposure of gut mucosa to carcinogenic heterocyclic amines, polycyclic aromatic hydrocarbons, 47 and nitroso compounds. 48,49 Unlike the current study that did not find a strong relationship between diet and CRC, two previous studies demonstrated a significant relationship between plasma phospholipids and CRC. 50,51 As previously mentioned, poor documentation could have contributed to this negative finding.…”
Section: Dovepresscontrasting
confidence: 99%
“…46 The risk of development of CRC due to a high-fat diet is thought to be due to exposure of gut mucosa to carcinogenic heterocyclic amines, polycyclic aromatic hydrocarbons, 47 and nitroso compounds. 48,49 Unlike the current study that did not find a strong relationship between diet and CRC, two previous studies demonstrated a significant relationship between plasma phospholipids and CRC. 50,51 As previously mentioned, poor documentation could have contributed to this negative finding.…”
Section: Dovepresscontrasting
confidence: 99%
“…Of course, a great many studies in the past few decades have identified novel prognostic biomarkers (39)(40)(41). Various studies have found that angiogenesis plays an important role in recurrence and metastasis (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the role of noncoding RNAs such as miRNAs, long non-coding RNAs, and circular RNAs has been recognized in the pathogenesis of different diseases including cancer [ 26 ]. CRC is one of the most frequent neoplasms in the world and 1.9 million new CRC patients were diagnosed in 2020 [ 27 ]. So far, the involvement of a number of circular RNAs including ciRS-7-A [ 28 ], circITGA7 [ 29 ], PIP5K1A [ 30 ], GLIS2 [ 31 ], and HIPK3 [ 32 ] in the development of colorectal cancer has been identified.…”
Section: Discussionmentioning
confidence: 99%